Early supplemental parenteral nutrition is associated with reduced mortality in critically ill surgical patients with high nutritional risk. Issue 12 (December 2021) - Sim, Joohyun; Hong, Jeong; Na, Eun Mi; Doo, Seorin; Jung, Yun Tae
Summary: Background & aims: Adequate nutritional provision is important for critically ill patients to improve clinical outcomes. Starting enteral nutrition (EN) as early as possible is recommended and preferred to parenteral nutrition (PN). However, patients who undergo emergency abdominal operations may have alterations in their intra-abdominal environment and gastrointestinal motility leading to limitation in starting an enteral diet. Therefore, our study was designed to evaluate the benefit of early supplemental PN to achieve adequate calorie and protein supply in critically ill patients undergoing surgery who are not eligible for early EN. Methods: We reviewed the medical records of 317 patients who underwent emergency abdominal surgery for complicated intra-abdominal infection (cIAI) between January 2013 and December 2018. The nutritional data of the patients were collected for 7 days in maximum, starting on the day of intensive care unit (ICU) admission. The patients were divided by low or high malnutrition risk using the modified Nutrition Risk in Critically ill (mNUTRIC) score and body mass index. The low- and high-risk groups were subdivided into the following two categories: those who received PN within 48 h ("early") and those who did not ("usual"). Data regarding the baseline characteristics, initial severity of illness, morbidity, and mortality rates were also obtained. The average calorie and protein supply per day were calculated in these groups. Results: Patients in all groups showed no significant differences in baseline characteristics, initial status, and infectious complications. In terms of outcomes, patients with low malnutrition risk had no significant difference in mortality. However, among patients with high malnutrition risk, the "Early" group had lower rates of 30-day mortality (7.6% vs. 26.7%, p = 0.006) and in-hospital mortality (13.6% vs. 28.9%, p = 0.048) than those of the "Usual" group. Kaplan–Meier survival curves for 30-day mortality in these groups also showed a statistically significant difference (p = 0.001). The caloric adequacy of the "Early" group and the "Usual" group were 0.88 ± 0.34 and 0.6 ± 0.29, respectively. Amounts of protein received were 0.94 ± 0.39 g/kg in the "Early" group and 0.47 ± 0.34 g/kg in the "Usual" group, respectively. There was no significant difference in infectious complications between both groups. Conclusions: Mortality in patients with high malnutrition risk who received early PN supply within 48 h after emergency surgery for cIAI was lower than those who did not receive PN earlier. PN may be necessary to fulfill the caloric and protein requirements for critically ill patients who cannot achieve their nutritional requirements to the fullest with EN alone.